Effect of Phytase Supplementation on the Performance of Babcock-380 Layer Hens (Journal of Tropical Resources and Sustainable Science (JTRSS), 2013)
In order to examine the effect of phytase supplementation in the diet of laying hen this experiment was conducted with 30 commercial hybrid Babcock-380 layers of 73 weeks of age. The hens were grouped into 3 treatment groups and given microbial phytase (Rena Phytase 400) at levels 2.5, 1.5 and 0 (control) g/kg feed in addition to their basal diet (110 g commercial pellet/day). Records on egg production/group/day, egg mass weight/day, body weight of hens at the end of experimental period were taken and analysed. Results revealed that hen house egg production (HHEP) and egg weight (EW) varied (p0 g/kg feed phytase group and all the means were significantly (p
Keywords: Microbial phytase; laying hen; egg weight